The Epoch of Universalism 1769-1989 / L'époque de l'universalisme 1769-1989 - Hofmann, Franck; Messling, Markus (Beyond Universalism / Partager l'universel, 2020)
2019 marked both the 30th anniversary of the fall of the Berlin Wall and Napoléon's 250th anniversary. Picking up on this contingency of world history with an ironic wink, the volume analyses in retrospect the epoch of European universalism. It focusses on its dialectics, polemically addressing and remembering both 1769 and 1989.